Rare occurrence of occult hepatitis C virus in apparently uninfected injecting drug users: a two‐centre, masked, case–control study. Issue 10 (17th April 2013) - Sugden, P. B.; Pham, T. N. Q.; Ratnarajah, S.; Cameron, B.; Bull, R.; White, P. A.; Michalak, T. I.; Lloyd, A. R.; ,
Summary: Occult hepatitis C virus (HCV) is a phenomenon where serum HCV RNA is not detected by sensitive commercial assays, but viral RNA is detected by ultrasensitive techniques. Occult HCV infection has not previously been studied in highly exposed, but apparently uninfected (EU) individuals. Two studies examining occult infection in EU subjects were undertaken – an initial two‐centre, masked, case–control study based on cross‐sectional samples ( n = 35 subjects) and a single‐centre confirmatory study based on longitudinal samples ( n = 32 subjects). Plasma and peripheral blood mononuclear cells were tested for HCV RNA using an ultrasensitive nested polymerase chain reaction assays. Two EU subjects in the first study (10%) and one in the second study (3%) were found to have consistently detectable HCV RNA. Occult HCV infection occurs in high‐risk, apparently uninfected subjects.